ULUMUL HADIS (Aspek Ontologis, Epistemologis dan Aksiologis) - Kurnia Munir; Ali Ngampo (AL-BAYAN INSTITUTE, 2024)
This study examines Ulumul Hadith through three main approaches in the philosophy of science ontology, epistemology, and axiology in order to provide a comprehensive understanding of the nature, sources of knowledge, and practical value of hadith science in the lives of Muslims. The issue underlying this study is the necessity for a more holistic and philosophical approach to understanding hadith, considering the ongoing intellectual and socio-religious challenges. The aim of this research is to describe the existence of hadith as an object of study (ontological), the process by which hadith knowledge is scientifically acquired (epistemological), and its contribution to social life (axiological). This study employs a qualitative descriptive method using a literature review approach by analyzing various classical and contemporary references related to hadith science and the philosophy of science. The findings show that from an ontological perspective, hadith holds a position as an authentic source of Islamic teachings originating from the Prophet Muhammad (peace be upon him). Epistemologically, hadith is accepted through a rigorous transmission system to preserve the authenticity of its content. From an axiological standpoint, hadith serves not only as a legal source but also plays a vital role in the moral and spiritual development of Muslims. The conclusion of this study asserts that the integration of ontological, epistemological, and axiological aspects in Ulumul Hadith is essential to develop a relevant and contextual understanding of hadith amid the dynamics of modern life.